Innovative Strategies for SMEs in East Java: Boosting Competitiveness Through Digital Marketing and E-Commerce - Salim, Agus; Sudarmiatin Sudarmiatin; Agus Hermawan (Jurnal Manajemen Bisnis Digital Terkini, 2026)
This study aims to analyze innovative strategies that can be implemented by Micro, Small, and Medium Enterprises (MSMEs) in East Java to improve competitiveness through digital marketing and e-commerce. This study uses a descriptive qualitative approach with a library research method by reviewing various scientific literature, government reports, and previous studies related to MSME innovation and digital transformation. The results of the study indicate that digital marketing and e-commerce innovation can increase market reach, operational efficiency, product differentiation, and MSME sales. However, the implementation of innovation still faces several challenges such as low digital literacy, limited capital, limited technology, and lack of system integration. Therefore, innovative strategies are needed, including integrated digital marketing, marketplace optimization, social commerce, digital payment systems, logistics integration, digital branding strengthening, and digital literacy training. In addition, collaboration between MSMEs, government, universities, communities, and digital platforms is an important factor in accelerating MSME digital transformation. This study produces recommendations for an innovative strategy model based on digital marketing and e-commerce to improve the competitiveness and sustainability of MSMEs in East Java.